Kajian Pengawasan Pemanfaatan Sumberdaya Air Tanah di Kawasan Industri Kota Semarang - Deo Valentino (Jurnal Wilayah dan Lingkungan, 2013)
Industrial estates in various activities, need clean water in relatively large amounts. Since the provision of clean water from PDAM is inadequate, hence the preference shifted to the industrial alternative source of water the soil. Utilization and monitoring conservation and utilization of ground water, has not held with as it should. Seeing this problem, the research question raised is how to control the utilization and conservation of ground water in Semarang City Industrial Zone? The purpose of this study was to assess the utilization of ground water monitoring by the government in the industrial city of Semarang. To achieve this goal the approach of this study using quantitative descriptive models, the respondents are managers of industrial areas, Central Java Province Department of Energy and Mineral Resources, PSDA Semarang, Semarang City BLH and DPKD Semarang. The analysis includes the analysis of the characteristics of the industries that use ground water, judging from the type and number of industries, water volume requirements, number of wells and the depth, availability of PDAM network, and industrial sites. Subsequent analyzes were analyzed for monitoring ground water resource utilization by BLH Semarang, Central Java province EMR, PSDA Semarang, Semarang City and DPKD. Based on the analysis of this research, note that the entire industrial area has a tendency to use ground water than PDAM water. However, many managers were not able to show the license artesian wells operated and have not made conservation efforts. Research also showed PSDA City, EMR Provincial and City BLH have not do routine monitoring to industrial units that use ground water related activities, so the level of supervision is considered weak. If the findings of this study are not immediately fixed in earnest, the potential threat of a water crisis can occur in the city of Semarang. In order to anticipate the potential impact of the utilization of ground water that does not take place as it should, this study offers recommendations: industrial area managers need to improve the discipline of recording and reporting of the various characteristics of the utilization and conservation of ground water utilization in compliance with existing legislation; agencies need improve the quality of ground water utilization monitoring; researcher / activist conservation of ground water need to do a more comprehensive study to find the real condition of the ground water at this point in the industrial city of Semarang.